Self-electrochemiluminescence of CdTe nanocrystals capped with 2-diethylaminoethanethiol. Issue 39 (2nd May 2017) - Han, Ting-Ting; Dong, Hao; Ren, Lu-Lu; Bao, Ning; Wu, Wenzhuo; Ding, Shou-Nian
Abstract : The self-electrochemiluminescence of CdTe nanocrystals capped with 2-diethylaminoethanethiol was achieved via protective reagent exchange. Abstract : We successfully synthesized 2-diethylaminoethanethiol (DEAET)-protected CdTe nanocrystals (CdTe-DEAET NCs) by exchanging DEAET onto 3-mercaptopropionic acid (MPA)-capped CdTe NCs (CdTe-MPA NCs) for the first time. Noticeable blue-shifts on the UV-vis absorption and photoluminescence spectra, the decrease of particle sizes and strong anodic ECL emission from CdTe-DEAET NCs were observed.